Cost effectiveness of wayside derailment detection - Schöbel, Andreas; Maly, Thomas (Univerzita Pardubice, 2010)
Wayside train monitoring systems are an important issue of modern railway operation due to the fact that more and more stations will become remote controlled by an operation centre. Therefore the task of monitoring fault states on moving vehicles has to be overtaken by autonomous sensor systems. Based upon the background of liberalized railway market it cannot be guaranteed that every vehicle is equipped with necessary sensors for fault state monitoring when passing the network of an infrastructure manager. Therefore each infrastructure manager has to install wayside equipment to check passing vehicles for fault states occurrences. The worst case scenario of not recognized fault states in time is a derailment. If preventing monitoring systems are not able to detect derailment indications in an early stage, the derailment itself must be identified by dedicated devices e.g. wayside derailment detectors. For safety related usage in a whole railway network the number of necessary wayside installations has to be identified in context to financial feasibility. To solve these questions a methodology was developed at Vienna University of Technology to estimate the potential costs and benefits under consideration of operational boundary conditions. Costs are directly related to the number of implemented derailment detectors, whereas benefit can be argued by reduced length of destroyed superstructure in case of a derailment. The braking behavior of different trains and the points on a line are the boundary conditions for practical implementation of this approach.
Keywords: wayside train monitoring; derailment detection